2011
DOI: 10.1016/j.camwa.2010.08.101
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy automata system with application to target recognition based on image processing

Abstract: a b s t r a c tIn order to get better image processing and target recognition, this paper presents a fuzzy automata system to target recognition. The system first performs image processing, and then accomplishes the target recognition. The system consists of four parts: image preprocessing, feature extraction, target matching and experiment. Compared with existing approaches, this paper uses both global features and local features of the target image, and carries out target recognition by using a fuzzy automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Several fuzzy automata (FA), i.e., FDFA, FNFA, FFA and FIA had been introduced, as well as the equivalence among several FA was discussed in previous works [1] [2]. Thus, the partial relation of several FA is introduced as follows.…”
Section: Discussion Of Relation Of Several Fuzzy Automatamentioning
confidence: 99%
See 1 more Smart Citation
“…Several fuzzy automata (FA), i.e., FDFA, FNFA, FFA and FIA had been introduced, as well as the equivalence among several FA was discussed in previous works [1] [2]. Thus, the partial relation of several FA is introduced as follows.…”
Section: Discussion Of Relation Of Several Fuzzy Automatamentioning
confidence: 99%
“…The extraction algorithm of various fuzzy automata had been discussed by using the neural networks in detail [1] [2]. To the extracted FA, its stability had been also described [1].…”
Section: Introductionmentioning
confidence: 99%
“…Astrain et al [10] suggested how to measure the fuzziness between the strings. Wu et al [16] explained the fuzzy automata system to achieve improved image processing and target recognition. Using fuzzy finite automata system, firstly good image processing achieved and then carried out for the target recognition.…”
Section: Application Of Fuzzy Automatamentioning
confidence: 99%
“…There are also applications of FA recently reported: Schmidt and Boutalis ( [4]) use fuzzy discrete event systems (FDES) in combination with multi-objective control for robot navigation; Wu, Pang and Han ( [5]) apply FA for target recognition based on image processing, and Bailador and Triviño use temporal fuzzy automata for pattern recognition ( [6]). …”
Section: Introductionmentioning
confidence: 98%